Overview Metode Fitoremediasi Dalam Pengelolaan air Tercemar Timbal (Pb): Overview of Phytoremediation Methods in Management of Lead (Pb) Polluted Water - Leka, Emil Salim Kahmi; Cahyadi, Tedy Agung; Nurkhamim, Nurkhamim; Ernawati, Rika; Winarno, Eddy (Media Ilmiah Teknik Lingkungan (MITL), 2024)
Wastewater originating from industry varies greatly depending on the type of industry. Industrial wastewater usually contains many toxic and dangerous chemical compounds (B3) and contains heavy metals. Heavy metals are pollutants that have dangerous effects because they cannot be broken down biologically and stable. Heavy metal elements can be distributed on the earth's surface in water, soil and air. Heavy metal waste pollution containing lead (Pb) is a problem for current environmental conditions. Heavy metals are found in almost all types of industrial waste. The increasing number of industries will cause increased pollution of water sources originating from industrial waste. . Therefore, effective and efficient methods are needed to manage lead-contaminated water. Methods that are easy to apply, low cost and environmentally friendly are highly desirable for managing lead-contaminated water so that the concept of good mining practice can be applied to sustainable development. The most efficient and effective method applied for mining waste management is the phytoremediation method. The results of the research state that several plants have a significant and efficient effect in helping the absorption of the metal lead (Pb) contained in water. Great Duckweed (Spirodela Polyrhiza) and Water Hyacinth (Eichhornia crassipes) are plants that are suitable for implementing phytoremediation methods in managing water contaminated with lead (Pb).